O dispositivo penitenciário no Brasil: disputas e acomodações na emergência da gestão prisional - Melo, Felipe Athayde Lins de (2018)
This thesis deals with the emergence of prison management in Brazil, understanding it as an effect of forces between different orders of the penitentiary dispositive, in which the Justice and Security bundles are highlighted, based on disputes and accommodation between actors, institutions and perspectives that, within each order or in their external interactions, configure the dynamics of the Brazilian Penitentiary Administration, within which a penitentiary bureaucracy is produced, specialized in mediating the conflicts and the approximations between the orders. In recent times, these mediations also suffer the influence of a third line of force, represented by the criminal groups originating inside prisons. The research was carried out through different methods, including an exegesis of texts on punishment, imprisonment and, in particular, Brazilian prisons, as well as the analysis of national and international documents and regulations. The grammars of this penitentiary bureaucracy, in turn, were examined in conjunction with a literature on the formation of civil public service in Brazil. In addition, interviews with prison policy managers in different states, informal dialogues with criminal servants and visits to prisons and other organs or institutions of the criminal justice system were conducted. Also heard were persons deprived of their liberty and their families, in an interaction between research and professional activity that allowed specific conditions of access to the field. The results point to a constant updating of the Brazilian penitentiary dispositive, which operates in the sense of ensuring its reproduction through different strategies of accommodation of the Law resulting from the preponderance of Security in the correlation of forces, which is manifested in the composition, functioning, characterization and processes of professional training of the penitentiary bureaucracy, understood as a diffuse and fragmented body that, far from characterizing a rationalization of the prison system, manifests itself mainly as a governing mentality.